On understanding familiar and less-familiar figurative language - Giora, Rachel; Fein, Ofer (Journal of pragmatics, 1999)
Findings of three experiments are consistent with the graded salience hypothesis (Giora, 1997), according to which salient meanings should be processed initially before less salient meanings are activated. A meaning of a word or an expression is considered salient if it can be retrieved directly from the mental lexicon. According to the graded salience hypothesis, processing familiar metaphors (which have at least two salient interpretations — the literal and the metaphoric) should involve activation of both their metaphoric and literal meanings, regardless of the type of context in which they are embedded. Processing less familiar metaphors (which have only one salient meaning — the literal) should activate the literal meaning in both types of contexts; however, in the literally biased context, it should be the only one activated. Processing familiar idioms in a context biased towards the idiomatic meaning should evoke their figurative meaning almost exclusively, because their figurative meaning is much more salient than their literal meaning. However, processing less familiar idioms in an idiomatic context should activate both their literal and idiomatic meanings, because both meanings enjoy similar salience status. In a literally biased context, familiar idioms should evoke their more salient idiomatic meaning to a greater extent than less familiar idioms. A word fragment completion test was used to measure the amount of activation of literal and figurative meanings in both literally and figuratively biased contexts. Subjects were presented with ‘target sentences’ (metaphors or idioms) at the end of either figuratively or literally biased contexts. They were asked to complete fragmented words (such as t_b_e) with the first word that came to mind. The target words were related to either the figurative or the literal meaning of the target sentence, so that activation of the different meanings could be assessed. Findings reveal that, contrary to current beliefs, metaphor interpretation involves processing the literal meaning. They further reveal that metaphor and literal interpretations do not involve equivalent processes.